Armed Drones under International Humanitarian Law - Hama Jan Aziz, Peshraw; Ahmad Xdir, Arazu (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Technological advancements in the twenty-first century reveal just another type of military-loaded weapons and equipment, drones which was the most prominent. The rise in military conflicts، as well as their increased use, and the absence of clarity provisions to arrange them, present challenges to some provisions of public international law in general, and international humanitarian law in particular. Recent years have demonstrated that international humanitarian law, when applied to international and internal armed conflicts, appears powerless in the face of technological advances in weapon manufacturing. As a result, it violates international humanitarian law's objective of providing the uppermost level of protection for civilians. This research attempts to assess the performance of drones in armed conflicts using basic rules of international humanitarian law such as the principle of distinction and proportionality and Necessity. the application of these regulations in many circumstances violates basic instructions of international humanitarian law. The international community must work diligently to prohibit or regulate its use.